Enhanced tight finite key scheme for quantum key distribution protocol to authenticate multi-party systems in cloud infrastructure - Khalid, Roszelinda (2018)
The aim of this study was to propose a unique communication protocol for authentication scheme for cloud infrastructure in replacing the key distribution technique based on public key infrastructure to achieve unconditional security in cloud with enhanced tight finite key. Currently, there are certain issues pertaining to confidentiality, integrity and authenticity in cloud systems. In our research we propose the use of quantum theory to transfer the authentication key via quantum channel. Referring to quantum theory, every key that we transform into bits cannot be cloned. This QKD protocol is believed to be able to detect any eavesdropping activities and provide an effective security. The Quantum Key Distribution (QKD) protocol used the concept of Multiparty QKD (MQKD) which allows the same key to be distributed to different parties based on quantum mechanism. A quantum key server generates a secret key that may strengthen the security aspects. A quantum key distribution key scheme is imposed in the cloud network to secure the top-secret message or information and capture the eavesdropper. The existence of quantum key storage between the cloud provider and cloud client may guarantee the integrity of communication process that ensures the party is authenticated and the communication cannot be intercepted. We propose the enhanced tight finite key scheme for quantum key distribution (QKD) protocol to authenticate multi-party system in cloud infrastructure. The main attraction is to provide a secure channel between a cloud client to establish a connection among them by applying the theories from Von Neumann and Shannon entropies and also Shor's algorithm. By generalizing these theories we will produce enhanced tight finite key scheme for quantum key distribution (QKD) protocol to authenticate multi-party system in cloud infrastructure. Hence we are using quantum channel and also quantum key distribution (QKD) together with BB84 protocol replacing common channel to distribute the key. The result shows that our proposed method could improve the error rate. This is due to any noise, interference, distortion or bit synchronization during the transmission of the initial key that error rate can be slightly reduced the error rate by implementing our new scheme. In other words it can push aside any interference during the key transmission. Our result shows the authentication level is increased to 30% compared to existing methods proposed by other researchers. In general, the current authentication scheme being used is still relatively backward methods especially in cloud environment. Many of the key aspects of authentication cannot guarantee effective control, especially in data transmission via a public channel. From the result we can see there is a significant result on reducing the error rate, enhanced the authentication level and reduce the possibility of any kind of threat. The simulation results show that our proposed scheme provides a strong authentication mechanism. It shows by the low amount of error rate while the key is distributes among others. In addition, our results show that the proposed scheme could reduce amount of information leak.